(untitled) (Heritage, 2021)
The Russian Formal School was active between 1915 and 1930 and represents one of the most influential directions in literary theory. Our intention was to present the main points of action of this school and to revalue some of its postulates as well. Views of members of the Russian Formalism that we analyzed were illustrated by examples from the story "Plod črevo tvojego" by Vidosav Stevanović. Our analysis has shown that the Russian Formalism is much more modern as a literary school than is most commonly thought.